FIELD-EMISSION SEM IMAGING OF COMPOSITIONAL AND DOPING LAYER SEMICONDUCTOR SUPERLATTICES - Perovic, D; Castell, M; Howie, A; Lavoie, C; Tiedje, T; Cole, J (1995)
Field-emission scanning electron microscopy (FE-SEM) has been used to study several semiconductor multilayer heterostructures. Compositional superlattices based on GexSi1-x/Si and AlxGa1-xAs/GaAs have been studied in both cross-sectional and oblique plan-views after indentation. Secondary and backscattered electron images reveal strong atomic number contrast which is primarily structural in origin. Secondly, for the first time, heterostructures containing n and p doping have been directly imaged at low voltages (0.5-1 kV) including: (i) Si- and Be-doped GaAs layers and (ii) B- and As-doped Si layers. Secondary electron images reveal strong contrast at doping concentrations as low as 10(17) cm(-3). The results have been interpreted in terms of energy band-bending effects between n- and p-doped layers.